Mathematical Model of the Deaeration of Finely Dispersed Solid Media in a Spherical Matrix of a Roller-Type Apparatus - Kapranova, Anna; Tarshis, Mikhail; Badaeva, Natalya; Sheronina, Irina (Frontiers in Energy Research, 2021)
The technological features of the production and transportation of some solid finely dispersed products of the chemical industry require the use of an additional deaeration operation (compaction). This processing of powders affects the quality of the product, delivery conditions. The production of deaerated granules-spheres from mineral components and bitumen for the preparation of asphalt concrete mixture or from powders for the production of dry dyes is relevant. The aim of this work is the mathematical modeling of the deaeration (compaction) process of solid finely dispersed media in a gap with perforated hemispherical shapes on the surfaces of the shaft and conveyor belt within the framework of the mechanics of heterogeneous systems. The distinctive features of the proposed method for modeling mechanical deaeration, as a technological process, from the known classical models are as follows. First, the plane-deformation model is described neglecting the forces of interphase interaction. The model assumes consideration of the movement of: a) the components of the solid skeleton of the dispersed medium together with the carrying phase as a whole; b) gas in an isothermal state through the pores of a finely dispersed material. This work is devoted to the study of part (a), i.e. behavior of the solid particle-gas system as a whole. Second, the compressibility of the solid particle-gas mixture is taken into account in the absence of elastoplastic deformations of the particles themselves. The efficiency of the seal-deaerator for solid finely dispersed media is estimated using the obtained analytical dependencies for the main strength and speed indicators of the process under study. Using the example of the deaeration of kaolin, the change in the degree of compaction of the resulting sample of a spherical granule with specified strength characteristics is investigated. It is shown that for the initial time interval up to 3.7⨯10-2 s, the growth of the porosity value relative to the horizontal coordinate along the conveyor belt is exponential and increases by a factor of 1.1. After eight such time intervals, the porosity values stabilize along the indicated coordinate with an increase of more than 1.4 times from the initial value.